Prefrontal Cortex Activity Is Associated with Biobehavioral Components of the Stress Response - Wheelock, Muriah D.; Harnett, Nathaniel G.; Wood, Kimberly H.; Orem, Tyler R.; Granger, Douglas A.; Mrug, Sylvie; Knight, David C. (Frontiers in Human Neuroscience, 2016)
Contemporary theory suggests that prefrontal cortex (PFC) function is associated with individual variability in the psychobiology of the stress response. Advancing our understanding of this complex biobehavioral pathway has potential to provide insight into processes that determine individual differences in stress susceptibility. The present study used functional magnetic resonance imaging (fMRI) to examine brain activity during a variation of the Montreal Imaging Stress Task (MIST) in fifty-three young adults. Salivary cortisol was assessed as an index of the stress response, trait anxiety was assessed as an index of an individual’s disposition towards negative affectivity, and self-reported stress was assessed as an index of an individual’s subjective psychological experience. Heart rate and skin conductance responses were also assessed as additional measures of physiological reactivity. Dorsomedial PFC, dorsolateral PFC, and inferior parietal lobule demonstrated differential activity during the MIST. Further, differences in salivary cortisol reactivity to the MIST were associated with ventromedial PFC and posterior cingulate activity, while trait anxiety and self-reported stress were associated with dorsomedial and ventromedial PFC activity respectively. These findings underscore that PFC activity regulates behavioral and psychobiological components of the stress response.